2022
DOI: 10.3390/cancers14020268
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Leptin, Proinflammatory Cytokines and Oxidative Stress with Tumor Size and Disease Stage of Endometrioid (Type I) Endometrial Cancer and Review of the Underlying Mechanisms

Abstract: Endometrioid endometrial cancer is associated with increased BMI and obesity through multiple pathogenetic mechanisms involving hyperestrogenism, hyperinsulinemia, altered adipokine secretion, inflammation, and oxidative stress. In the present study, we aimed to investigate the correlation between BMI, leptin, the proinflammatory cytokines IL-6 and TNFα, reactive oxygen species (ROS), and the traditional prognostic factors T, G, N and M status among type I endometrioid and type II endometrial cancer patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 69 publications
(81 reference statements)
1
12
0
Order By: Relevance
“…Leptin is among the most important adipokines during EC development, and numerous recent studies have already proposed it as a new candidate marker in determining the potential risk of EC ( 42 45 ). In accordance with the literature ( 46 50 ), our study showed higher leptin levels in EC patients, particularly in Type I EC, at higher stages and in patients with present metastasis or MI and LVI.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Leptin is among the most important adipokines during EC development, and numerous recent studies have already proposed it as a new candidate marker in determining the potential risk of EC ( 42 45 ). In accordance with the literature ( 46 50 ), our study showed higher leptin levels in EC patients, particularly in Type I EC, at higher stages and in patients with present metastasis or MI and LVI.…”
Section: Discussionsupporting
confidence: 93%
“…observed that BMI and diabetes appeared to affect the association between leptin levels and EC risk ( 43 ). Some other studies found a strong positive correlation between patients’ BMI and serum leptin levels ( 46 , 50 ), while a recent Mendelian randomization analysis showed a causal effect of BMI on EC but failed to find evidence for leptin to be causally implicated in EC risk ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of IL-1α ( 22 ), IL-11 ( 57 ), IL-31 ( 27 ) and IL-33 ( 27 ) were observed in poor differentiated EC, while low level of IL-27 ( 20 ) and infiltration of IL-9 + lymphocyte ( 47 ) was recorded with the decrease of EC differentiation degree. Moreover, IL-6 ( 56 , 146 ), IL-8 ( 117 ), IL-31 ( 27 , 29 ) and IL-33 ( 27 , 29 ) were positively correlated with poor clinical characteristics including advanced stage, myoinvasion, and node or distant metastases. Therefore, in the future, these interleukins may be useful as the indicators for the management of EC, for example for the evaluation of whether lymph node dissection is necessary.…”
Section: Clinical Application Of Interleukins In Ecmentioning
confidence: 96%
“…Adipokines, a diverse group of biologically active substances, are characterized by adipose tissue secretion ( Trayhurn and Wood 2004 ). The levels of various adipokines, such as leptin ( Madeddu et al, 2022 ), visfatin ( Wang et al, 2019 ), galectin ( Boutas et al, 2021 ), resistin ( Ozgor et al, 2019 ), adiponectin ( Ellis et al, 2020 ), and vaspin ( Erdogan et al, 2013 ), are increased or decreased in endometrial cancer and significantly correlated with cancer progression ( Ray et al, 2022 ).…”
Section: Manuscript Formattingmentioning
confidence: 99%